Answer:
9
Step-by-step explanation:
cross multiply 7/63 by 1/x
so, multiply 7 by x and 63 by 1
you get 63=7x
divide by 7 on both sides and you get 9
I'm going to use the substitution method.
If y = - 3/2 - 7, then:
1/2x + 5 = - 3/2x - 7
Combine like terms:
4/2x = - 12. Mutiply both sides by 2/4 to get x = -12 (2/4)
Simplify to get:
x = - 6.
Plug - 6 back in for x in either equation.
Y = 1/2( - 6) + 5 which becomes Y = - 3 + 5.
X = - 6, Y = 2
Answer:
The constant factor between consecutive terms of a geometric sequence is called the common ratio.
Example:
To find the common ratio , find the ratio between a term and the term preceding it. r=42=2. 2 is the common ratio.
Answer:
B
Step-by-step explanation:
Answer:
223.56$
The ans is simple
Add all the given values
Then we get the ans
Step-by-step explanation:
The ans is simple
Add all the given values
Then we get the ans